Clot Retraction: A Miniaturized Hemoretractometer for Blood Clot Retraction Testing (Small 29/2016). Issue 29 (1st August 2016) - Li, Zida; Li, Xiang; McCracken, Brendan; Shao, Yue; Ward, Kevin; Fu, Jianping
Abstract : Whole blood coagulation testing provides valuable diagnostic information on diseases such as bleeding disorders, heart attack, deep venous thrombosis, etc. On page 3926, J. Fu and co‐workers develop a miniaturized hemoretractometer to measure clot contraction upon blood coagulation with good reproducibility and robustness. This device design shows great application potential in point‐of‐care testing. Photo credit: David Peyer from University of Michigan.